Numerical solution of mixed convection in a lid-driven cavity with arc-shaped moving wall. Issue 3 (2nd May 2017) - Ismael, Muneer A.
Abstract : Purpose: This paper investigates a numerical treatment to steady mixed convection in a lid-driven square cavity with arc-shaped moving wall or lid. The horizontal walls are thermally insulated. The vertical left wall is kept isothermally at high temperature, while the right arc-shaped moving wall is kept isothermally at low temperature. Design/methodology/approach: Finite difference method in Cartesian coordinates with the upwind scheme is used in numerical solution. The irregular curved boundary has been treated by invoking non-uniform mesh grid with the ability to generate boundary fitted nodes. Jensen's formulas of Neumann's boundary condition have derived for the non-uniform mesh grid. The arc-shaped moving wall is considered as a segment of a rotating cylinder; thus, the studied pertinent parameters are the rotational speed of the arc-shaped wall in both aiding and opposing directions ω = −1, 000-1, 000, the arc-wall radius Ro = 0.5099-1.534 which is governed by its center (X0, Y0 ) = (1.1, 0.5)-(2.45, 0.5) and the Rayleigh number Ra = 10 3 − 10 6 . Findings: The results have shown that for low Rayleigh numbers, the rotational speed enhances heat transfer irrespective to the direction of rotation, while for high Rayleigh numbers, the aiding anticlockwise rotation (negative ω) enhances the heat transfer, while the opposing clockwise rotation (positive ω) manifests a retardation effect on the heat transfer. For a motionless arc-wall, its radius is ineffective for aiding heat transfer, while for non-zero arc-shaped wall speed, the heat transfer is an increasing function of its radius. Originality/value: The arc-shaped moving wall has never been investigated until now. Therefore, the originality of this paper is due to studying the mixed convection in a lid-driven cavity with moving arc-shaped wall and inspecting the effect of its curvature and rotational speed in both directions on the flow and thermal fields.